2011
DOI: 10.1016/j.ijantimicag.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Confronting multidrug-resistant Acinetobacter baumannii: a review

Abstract: Multidrug-resistant Acinetobacter baumannii (MDR-AB) infections are difficult to treat owing to the extremely limited armamentarium. The present review reports all available treatment options against MDR-AB, including single molecules, combination schemes, and alternative modes of antimicrobial administration. Additionally, a group of recently reported peptides with anti-MDR-AB activity is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 138 publications
0
73
0
Order By: Relevance
“…Moreover, rifampicin has been proposed as an alternative antimicrobial agent for the treatment of MDR A. baumannii, based on outcomes of in vitro studies 2,7,8 and in vivo infection models 12,27 . A previous study has shown that 64% of MDR A. baumannii were susceptible to rifampicin 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, rifampicin has been proposed as an alternative antimicrobial agent for the treatment of MDR A. baumannii, based on outcomes of in vitro studies 2,7,8 and in vivo infection models 12,27 . A previous study has shown that 64% of MDR A. baumannii were susceptible to rifampicin 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by MDR A. baumannii are associated with high morbidity rates, especially in immunocompromised patients, patients admitted to intensive care units, and patients treated www.scienceasia.org with broad-spectrum antibiotics 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…It can survive for longer periods in hospital settings and is potentially capable of causing serious hospital outbreaks. Over the last 10 years, the clinical significance of A. baumannii has increased through its ability to acquire multi-drug resistance and so reduce therapeutic options [2]. In most hospital settings, it is increasingly associated with nosocomial pneumonia in intensive care units, particularly in patients with ventilator-associated pneumonia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…and Morganella spp. 22,38,54,55 However, evidence of increased mortality, compared to other antibiotic therapies, especially in ventilator-associated pneumonia 48 leads to caution in its use. Moreover, a serious drawback, at least for monotherapy in bacteremia, is the low serum level obtained.…”
mentioning
confidence: 99%
“…2,31,81,82 Many authors argue that rifampin should be considered for addition to other active antibiotics in the treatment of uncontrolled infection due to MDR bacteria, 31,55,78,[83][84][85] though there is little evidence of why rifampicin should improve outcome and no randomized trials to show that it does improve these outcomes. Further obstacles include: (a) there is no relevant in vitro breakpoint for susceptibility to rifampin against Gram-negative bacteria; (b) toxic potential of rifampin; (c) multitude of drug interactions between rifampin and other agents, a main concern especially in onco-hematological patients and allogeneic HSCT recipients who receive a lot of other drugs concomitantly (such as cyclosporine, mycophenolate mofetil, antifungals, antivirals).…”
mentioning
confidence: 99%